INDUCED BREEDING, EMBRYONIC AND LARVAL DEVELOPMENT OF CRITICALLY ENDANGERED FISH PUNTIUS SARANA (HAMILTON, 1822) UNDER CAPTIVE CONDITION - U. K. Udit; A. K. Reddy; P. Kumar; M. A. Rather; R. Das; D. K. Singh (Journal of Animal and Plant Sciences, 2014)
In the present study, Puntius sarana collected from Khandepar River were transported in live condition and acclimatized to captivity. The captive brood stock was successfully raised in FRP tank with a specially balanced fish diet and intermittently fed with Tubifex warms for a period of one month. Sex of brooders was identified based on morphological features – the abdomen was swollen in females, while it was firm and round in males.  Induced breeding of this species, with ovatide at 0.2 ml per male (180 g) and 0.3 ml per female (232-240 g) was achieved. Sex ratio of 2:1 and 1:1 (male: female) were maintained in two trials. The interval between injection and spawning was 8-9 hours. The average fertilization and hatching rates observed were 90.5% and 75.39 % respectively. The hatching period was observed to be 15-16 hours at water temperature 26.5-28.5°C. The diameter of fertilized eggs was 1.3mm. The result presented in this study acquaint with a step ahead for the inventory and conservation of commercial freshwater food fish, Puntius sarana in Indian Rivers. The originality of this work and its application is for the conservation purpose reside in the scope of studied species. The present work contributes to cover deficient information for Puntius sarana.
Keywords: Puntius sarana; brooders; breeding; conservation; hatchery